Evaluation of a pharmaceutical assessment screening tool to measure patient acuity and prioritise pharmaceutical care in a UK hospital. Issue 2 (31st May 2016) - Hickson, Ryan P; Steinke, Douglas T; Skitterall, Charlotte; Williams, Steven D
Abstract : Objective: A service evaluation project was conducted to design a pharmaceutical assessment screening tool (PAST) to assign all inpatients a patient acuity level (PAL) to then help teams of clinical pharmacists prioritise the frequency of, and the seniority of, pharmacists performing patient reviews; assess clinical pharmacists' adherence to the tool; and identify when pharmacists do not adhere to the tool. Methods: The PAST was developed by consensus methodology to prioritise departmental workflow for clinical pharmacists. The most pharmaceutically complex patients at the greatest risk of adverse drug events were expected to receive a PAL score of 3, while the least complex receive a PAL of 1. A quasi-experimental service evaluation study was conducted 6 months after implementation of the tool to quantify agreement between pharmacist-documented and expected per-guidance PALs. Patients were selected via random clusters from wards. For each patient, a PAL was calculated by the researcher and compared with the pharmacist-documented PAL. Results: 20 patients (57%) had documented PALs that matched the expected PAL based on pharmacy departmental guidance. Seven of nine patients with overvalued pharmacist-documented PALs had no high-risk medications and no organ dysfunction. Four of six patients with undervalued pharmacist-documented PALs had cystic fibrosis, who should all automatically score the maximum level. Conclusions: Until electronic health records allow the calculation of PALs automatically, the utilisation of the current tool may be improved by eliminating unclear and unused portions of the tool and reiterating the true purpose of the tool to all pharmacists.